Association Between Vitamin A Intake and Disease Severity in Early-Onset Heterotopic Ossification of the Posterior Longitudinal Ligament of the Spine. Issue 8 (October 2022) - Endo, Tsutomu; Imagama, Shiro; Kato, Satoshi; Kaito, Takashi; Sakai, Hiroaki; Ikegawa, Shiro; Kawaguchi, Yoshiharu; Kanayama, Masahiro; Hisada, Yuichiro; Koike, Yoshinao; Ando, Kei; Kobayashi, Kazuyoshi; et al.
Study Design: A sex- and age-matched case-control study and a cross-sectional study. Objective: In our previous study, patients with early-onset (<50 years of age) ossification of the posterior longitudinal ligament (OPLL) had distinct features such as morbid obesity, a high prevalence of lifestyle-related diseases, and diffuse ossified lesions mainly affecting the thoracic spine. Our goals were to determine whether early-onset OPLL patients have unbalanced dietary habits and to identify nutritional factors associated with OPLL exacerbation. Methods: In Study 1, the simple brief-type self-administered diet history questionnaire (BDHQ) was used to compare nutrient intake levels of early-onset OPLL patients (n = 13) with those of sex- and age-matched non-OPLL controls (n = 39) or with those of common OPLL (onset age ≥ 50 years, n = 62). In Study 2, serological validation was conducted for thoracic OPLL patients (n = 77) and non-OPLL controls (n = 101) in a nationwide multicenter study in Japan. Results: The BDHQ showed that the early-onset OPLL patients had significantly lower intakes of vitamins A and B6 than non-OPLL controls. These results were validated by lower serum vitamins A and B6 levels in the early-onset thoracic OPLL patients. The severity of OPLL negatively correlated with serum vitamin A levels in male early-onset OPLL patients. The multiple regression analysis revealed that the severity of thoracic OPLL had an association with onset age and serum vitamin A level. Conclusions: Vitamin A deficiency resulting from unbalanced dietary habits is associated with exacerbation of male early-onset OPLL.